Lab-grown insect meat - Chemical and biological insights - A comprehensive review - Siddiqui, S.A.; Ngah, N.; Wu, Yuan Seng *; Kalita, T.; Yudhistira, B.; Ibrahim, S.A. (Brill Academic Publishers, 2024)
Lab-grown insect meat is a promising alternative to traditional livestock for sustainable food production. This review paper aims to provide a comprehensive overview of the current state of knowledge regarding lab-grown insect meat, emphasizing key aspects such as life cycle assessment, insect cell culture history, technological advancements, and bio-robotics in insect cell culture. Comparisons and challenges between insect and mammalian/avian cell culture methodologies are presented. The nutritional content of edible insects (proximate, amino acid, mineral, and vitamin content) and the potential health benefits of consuming insect meat are discussed. The paper also explores embryonic and adult myogenesis processes in insect cells, as well as the significance of insect body fat and muscle cells in culture. Applications of insect cell culture in various fields, such as food production and pharmaceutical development, are presented. Moreover, the potential occurrence of mutations in lab-grown insect cells is examined. Lastly, the review addresses the drawbacks and limitations of insect labriculture, discussing factors such as scalability, cost-efficiency, and public acceptance. Overall, this comprehensive review provides essential insights into the chemical and biological aspects of lab-grown insect meat, paving the way for further research and development in this emerging field. This article is the first review article reporting the chemical and biological insights of lab-grown insect meat.